Islamic capital market and debt financing of Shariah-compliant firms in Indonesia - Haron, Razali; Adeyemi, Adewale Abideen (IIUM Press, International Islamic University Malaysia, 2016)
Islamic Capital Market (ICM) is expanding rapidly worldwide and Indonesia is following very closely. Examining 290 shariah-compliant Indonesian firms, we found that certain firm and industry level determinants do influence the debt financing without ignoring the shariah principles governing the decisions. The ICM accelerating growth is very much reflected in the findings, thus contributing significantly in the literature and to the policymakers as well. Being shariah-compliant does not hinder them from engaging in higher debt with Islamic debt instruments employed as alternatives.